Influence of water molar ratio on fabrication of silica ceramic membranes via sol-gel dip-coating method - Kahlib, Nor Amyra Zulianey; Wan Mazlan, Wan Amirah; Mohd Daud, Farah Diana; Mel, Maizirwan; Ahmad Azhar, Ahmad Zahirani; Hassan, Noor Azlina; Nor Hairin, Assayidatul Laila (UR Publishers, 2018)
Ceramic membranes are an inorganic membrane that received great attention as it overcome the limitation of polymeric membrane. The silica ceramic membrane can be used in gas separation as it able to work at elevated temperature and in chemically aggressive environment. This work is conducted to study the influence of the molar ratio of water (R) on the fabrication of silica ceramic membrane by sol-gel dip-coating method. Commercial support was dipped into the solutions consist of the mixture of tetraethylorthosilicate (TEOS), distilled water and ethanol with the addition of a small amount of acid as a catalyst. The molar ratio of TEOS toethanol was fixed at 1 to 3.8 (TEOS:ethanol, 1:3.8). However, the molar ratio of water are varied at 2, 3, 4 and 4.7. FESEM (Field Emission Scanning Electron Microscope), XRD (X-ray Diffraction) and FTIR (Fourier Transform Infrared Spectroscopy) are utilized to determine the structural and chemical properties of silica ceramics that are fabricated with different R. FESEM images implied that the silica has been deposited on the surface of silica membrane and penetrate into the pore walls. XRD analysis of the fabricated silica ceramic membranes illustrated the existence of silicate hydrate. The fabricated silica ceramic membrane with silica sol molar ratio 1:3:3.8 gave the lowest intensity of XRD peak. FTIR analysis, it was observed that the presence of Si-O-Si functional group is in the range 1060 to 1080 cm-1.